“Griekeland” to “Platteland”: appropriating the Euripidean Medea for the contemporary Afrikaans stage - Albertyn, Maria Adriana (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.